How Rootstocks Impact the Scion Vigour and Vine Performance of Vitis vinifera L. cv. Tempranillo - Alicia Pou; Luis Rivacoba; Javier Portu; Andreu Mairata; David Labarga; Enrique García-Escudero; Ignacio Martín (Australian Journal of Grape and Wine Research, 2022)
Background and Aim. The genetically determined characteristics of grapevine rootstocks are important factors that affect scion performance. This 3 years’ field study aimed to characterize the influence of four well-established 30-year-old rootstocks (110 Richter, 1103 Paulsen, 41B, and 161-49Couderc) on the Tempranillo cultivar in the semiarid wine growing region of D.O.Ca. Rioja, North-Eastern Spain. Methods and Results. Nutrient concentrations of mineral elements at flowering and veraison were determined in the vines, jointly with grapevine-water status, gas exchange, vine vigour, and chlorophyll content. Moreover, grapevine yield and grape quality were determined at harvest. The least vigorous rootstocks (41B, 161-49C) conferred drought adaptability traits by increasing water use efficiency (WUE) and decreasing whole-plant water conductance per unit leaf area (Kplant) compared to the more vigorous rootstocks (1103-P, 110-R). In contrast, the more vigorous rootstocks increased water transport capacity, which led to higher plant performance and nutrient uptake efficiency. At flowering, 1103-P and to a lesser extent, 110-R were most efficient at taking up nutrients, while 161-49C had the lowest concentrations for most nutrients. At veraison, 41B exhibited closer behaviour to 110-R than 161-49C, while 1103-P and 161-49C remained the most differentiated rootstocks, with higher and lower nutrient uptake, respectively. In addition, compared to the more vigorous rootstocks, the yield was up to 1.6 kg lower for the less vigorous rootstocks but the grape composition was improved. Notably, 161-49C led to higher total soluble solids, total acidity, and polyphenol content. Conclusions. Overall, grafting onto specific rootstocks represents a strategy to confer differential regulation of grapevine water-saving strategies, yield, berry quality, and nutrient uptake potential. Significance of the Study. This information may be useful for growers seeking to develop a site-specific selection of rootstocks for the grafted Tempranillo cv.